Design of a Watering Control System for Chili Seedlings Using Arduino Uno - Ramadhani, Syarifah Fitrah; Lasulika, Mohamad Efendi; Bode, Andi; Djailani, Moh. Adrian; Posumah, Risky Randa (International Journal Software Engineering and Computer Science (IJSECS), 2024)
Technology in agriculture has brought revolutionary changes in the way we view and treat food production. This research is the design of a watering control system because controlling plant watering is an important factor in healthy plant growth. With the use of technology such as Arduino Uno, designing an automatic watering control system that can monitor soil moisture, regulate watering according to plant needs, besides that, another goal is to increase agricultural productivity by optimizing watering of chili plants. The results of research and testing that have been carried out, the Arduino Uno based automatic plant irrigation tool shows success in its design and operation; this tool has been designed and made using an Arduino Uno microcontroller and YL-69 sensor, as well as other supporting devices, which function according to their purpose and function with good performance in automatic watering. This tool can work effectively when the humidity sensor sends data to the Arduino, where if the received data is below the specified limit, the relay automatically activates the water pump to perform watering. During the process, if the sensor detects soil moisture levels above the limit, the relay will turn off the pump and stop watering